Pengembangan Mobile Module Fisika Berbasis Problem Based Learning Pada Materi Suhu dan Pemuaian di SMK - Afrian, Zain; Ellianawati, Ellianawati; Susilo, Susilo (UPEJ Unnes Physics Education Journal, 2020)
This study aims to produce a Physics Mobile Module (Moba MOP) based on Problem Based Learning (PBL) which is feasible on the topic of temperature and expansion. The method used is research and development (R&D) with the 4D model, consisting of the stages of define, design, develop and dessiminate. In this research, only up to the develop stage. The resulting product is Moba MOP learning media in the form of an android application which is presented with the stages of a problem-based learning model. The results showed that the Moba MOP application based on problem-based learning was feasible based on the validation results of 3 experts by obtaining an average score with good criteria in terms of content, language, presentation and graphic aspects.